Fingertip-Coupled Spindle Signaling Does Not Contribute to Reduce Postural Sway Under Light Touch - Silva, Cristiano Rocha; Magalhães, Fernando Henrique; Kohn, André Fabio (Frontiers in Physiology, 2019)
The details of how light touch (LT) of a stable surface reduces postural sway are still not well known. We hypothesized that removal of feedback provided by muscle afferents of the touching fingertip would increase postural sway in standing subjects. Eleven participants stood upright on a force plate with eyes closed and on an unstable surface. The experimental conditions involved two different finger positions: PMA [with partial muscle afferents], which includes sensory information from the fingertip flexor muscles; and NMA [no muscle afferents], without information from either fingertip flexor or extensor muscles. In the control condition, the participants kept the same posture, but with no finger touch (NT). Postural sway in both anteroposterior (AP) and mediolateral (ML) axes were recorded. Results showed that LT decreased all sway quantifiers as compared with the NT condition. The withdrawal of information from the touch finger muscle afferents (NMA condition) did not increase postural sway. Actually, there was a small, albeit statistically significant, decrease in the variability of center of pressure displacement in the AP direction. These results indicate that in some cases muscle afferent input may either not contribute or even worsen the overall quality of sensory feedback from a given body segment, leading to no improvement or even a slightly decreased performance of the motor control system (evaluated by means of levels of postural sway in the present investigation). The results suggest that non-spindle fingertip afferents provide the bulk of the sensory feedback associated with the fingertip that is touching a ground-referenced object during quiet standing under LT.